(3JHUQI GdCPgGf aj fcJ GdeYGfi hGdHjGfs - (3GdTfbjWj , GdeNJGQ Hf Hhfg GdTfbjWj GdeZQHj,J (B1230 (3g` s
(3ChdgG (B:s
(3jbhd QGLi aVd QHg GdMeO ddg Ydeg GdHjGf ef dG dg ai GdhUa HGdeYGfi , hdGHOjY UfYg ef aGfi , OdJ Ydi CaVGdg hYOdg hJcTa GdZWG Yf GdObGFb hJXaQ GdCacGQ HGdMbGFb s
(3BNQgG (B:s
(3NGJeI ai GdSQbGJ GdTYQjI hef jcf ai ZQV ehGabkG eTJQc adG jYO SGQbkG s
(3GdfSNI HgG MhGTs
(3HgG BKGQ QWhHI hMhGagG eJBcdIs
(3HYV CHjGJgG eVHhWI HGdMeQI s
(3hHYV UaMGJgG eWehSI s
(3HgG fXGe GdJYbjHI s
(3fSNI bOjeI s
Keywords: (3GdHdGZIs